Consensus Building for Long‐term Sustainability in the Non‐North American Context: Reflecting on a Stakeholder Process in Japan. (28th July 2016) - Matsuura, Masahiro; Baba, Kenshi
Abstract: Practitioners of consensus building are stepping into a relatively new arena of practice: sustainability issues in the non‐North American context. This article explores challenges in such settings, which we illustrate, with a case in Japan regarding the promotion of wood biomass usage through stakeholder dialogue in a small island community. Reflection from the experience reveals two challenges that are likely to occur in similar contexts: drawing the attention of stakeholders to the long‐term risks to sustainability and dealing with personal relationships in a high‐power‐distance culture. We find that in our case and more generally stakeholders' problem recognition related to risk must be nurtured through learning opportunities and scenario exercises in the early stages of consensus building processes. The hierarchical nature of interpersonal communication in several Asian countries, where senior participants enjoy more power in negotiation, also requires careful design of processes, particularly when long‐term issues are at stake.